Photocatalytic Degradation of Textile Dye Cristal Violet Wastewater using Zinc Oxide as a Model of Pharmaceutical Threat Reductions - Ayad F. Alkaim (Journal of Global Pharma Technology, 2019)
The photo catalytic degradation of Cristal Violet   dye (CV) has been investigated under UV irradiation in aqueous suspension of zinc dioxide under a variety of conditions. The degradation was studied by monitoring the change in dye concentration using UV spectroscopic technique. The effects of key operation parameters such as initial dye concentration, catalyst loading, as well as light intensity on the decolonization extents were studied. And found The initial increase in rate of dye degradation with increase in amount of catalyst is due to increase in number of active sites on the surface of photo catalyst  the rate of photo catalytic degradation and photo degradation efficiency increased with increasing is increasing with increasing UV light intensity.Keywords: Photcatalytic; Cristal Violet dye, zinc oxide